2021
DOI: 10.1155/2021/5525112
|View full text |Cite
|
Sign up to set email alerts
|

MiR-122 Participates in Oxidative Stress and Apoptosis in STZ-Induced Pancreatic β Cells by Regulating PI3K/AKT Signaling Pathway

Abstract: At present, there are few reports concerning the relationship between miR-122 and diabetes. In addition, the effect of miR-122 on streptozotocin- (STZ-) induced oxidative damage in INS-1 cells remains unclear. The present study aimed to investigate the role and modulatory mechanisms involving miR-122 in diabetes. STZ was used to induce INS-1 cell damage. Reverse transcription-quantitative PCR was used to investigate the expression of miR-122. A TUNEL cell apoptosis detection kit was used to detect apoptosis. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…The effects of MgT administration on regulating PI3K/Akt pathway, which was a classical pathway related to cell apoptosis[ 24 ], were also detected. As shown in Figure 4 , Aβ 25-35 -exposed cells showed lower ratios of phosphorylated (p)-PI3K/PI3K and p-Akt/Akt than control cells (both P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of MgT administration on regulating PI3K/Akt pathway, which was a classical pathway related to cell apoptosis[ 24 ], were also detected. As shown in Figure 4 , Aβ 25-35 -exposed cells showed lower ratios of phosphorylated (p)-PI3K/PI3K and p-Akt/Akt than control cells (both P < 0.001).…”
Section: Resultsmentioning
confidence: 99%
“…A recent study demonstrated that Rotundifuran-induced ROS production could lead to cell apoptosis via suppressing the PI3K/Akt pathway in the cervical cancer cell model[ 35 ]. Another study also showed that inhibition of apoptosis was correlated with the ROS-mediated PI3K/Akt pathway in a streptozotocin-treated INS-1 cell model[ 24 ]. Based on the above findings, dysregulation of the PI3K/Akt signaling pathway supports the relationship between oxidative stress and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, disruption of miR-122 can effectively impede apoptosis and oxidative stress in STZ-induced INS-1 cells. This modulation is underpinned by a mechanism intricately associated with the PI3K/AKT pathway [ 72 ].…”
Section: Pi3k/akt Signaling Pathwaymentioning
confidence: 99%
“…69 Similarly, overexpression of miR-139-5p negatively regulated the expression levels of protein interacting with C-kinase 1 (PICK1), which normally provides functional protection of β-cells through PI3K/Akt activation. 70 Likewise, although their specific gene targets were not investigated, the inhibition of miR-122 71 or let-7 miRNA 72 resulted in the activation of PI3K/Akt signaling in β-cells, which mediated their protection from STZ-induced destruction in vitro 71,72 and in vivo. 72 Collectively, the aforementioned studies indicate that upregulation of PI3K/Akt signaling through dialogue with various miRNA can exert positive effects on β-cell function and survival, and, as such, these miRNA represent viable therapeutics/targets for the treatment of T1D.…”
Section: Modulation Of Microrna Expressionmentioning
confidence: 99%
“… 69 Similarly, overexpression of miR‐139‐5p negatively regulated the expression levels of protein interacting with C‐kinase 1 (PICK1), which normally provides functional protection of β‐cells through PI3K/Akt activation. 70 Likewise, although their specific gene targets were not investigated, the inhibition of miR‐122 71 or let‐7 miRNA 72 resulted in the activation of PI3K/Akt signaling in β‐cells, which mediated their protection from STZ‐induced destruction in vitro 71 , 72 and in vivo. 72 …”
Section: Modulators Of Pi3k /Akt Signaling Are Pot...mentioning
confidence: 99%